Comparing the educational effect based on critical thinking and routine approaches on skills to manage of pre-eclampsia and persistence of knowledge of midwifery students - Zohre Mirkazehi rigi (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: Preeclampsia is a special syndrome of pregnancy and common cause of mothersﹸdeath associated with delay in diagnosis and nursing staff’s inappropriate control. The current study was carried out to compare the effect of training on method based on critical thinking and traditional education on maintenance of knowledge level and clinical skill of controlling preeclampsia in midwifery students. METHODS: The study was a clinical trial performed on 60 midwifery students at nursing and midwifery college of Mashhad in 1395. The participants were randomly divided in to two groups of training based on critical thinking and traditional education. The clinical skill of preeclampsia control in students of both groups were measured by an identical constructive test (six stations) before and a week after intervention. The data were analyzed by SPSS software and descriptive statistics such as Mann-Whitney, Fried man, and Wilcoxon tests. FINDINGS: The findings indicated that the mean scores of notice of preeclampsia control of both critical thinking and traditional education groups a week and a month after intervention showed a significant increase compared to before intervention (p<0.05 ). The scores of clinical skill of controlling preeclampsia in both groups of critical thinking and traditional education a week after intervention revealed a significant increase compared to before intervention (p<0.05). CONCLUSION: Clinical skill training based on the approach of reinforcement of critical thinking skill leads to better performance of midwifery students in nursing care process and can be used to improve the quality of midwifery studentsﹸclinical skills.